Pembelajaran inklusif dalam membangun keterampilan membaca pada siswa slow learner di SD Peradaban - Lulu Damayanty; Ujang Jamaludin; Firdaus Firdaus (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to describe the implementation of inclusive learning to develop reading skills among slow-learning students at Peradaban Elementary School. The background of this study is the importance of inclusive education in providing children with special needs opportunities to learn alongside children in general education classes. To investigate this, the research uses a qualitative, descriptive approach. Data collection in this study uses three techniques, namely observation, interviews, and documentation. Furthermore, the data analysis technique used the Miles and Huberman model. The data sources in this study included the inclusion coordinator, the fifth-grade homeroom teacher, the special assistant teacher, and students. The study's results indicate several key findings. First, there are difficulties in reading skills among slow learner children, namely in recognising letters of the alphabet, reading syllables, reading simple sentences, and reading comprehension. Second, teacher strategies for inclusive learning to develop reading skills include seating design, selection of models, methods, and learning media. Finally, there are supporting and inhibiting factors in the inclusive learning of reading skills among slow-learning students, namely a lack of teacher support, an inclusive classroom environment, a lack of self-confidence among children, and a need for motivation.